8.21 FOREIGN EXPERIENCE OF PROSECUTOR'S CONTROL OVER LEGISLATIVE IMPLEMENTATION IN TAX AUTHORITIES - Usmonov Mansurbek Muxammadjonovich Master study direction of the "prosecutor's activity" of the Academy of law enforcement of the Republic of Uzbekistan (Innovative technologies in construction Scientific Journal, 2024)
The state of affairs in the tax sphere is significantly influenced by such factors as the imperfection and inconsistency of the current legislation regulating the procedure for taxation and granting benefits, as well as bringing violators to justice; insufficient analysis of judicial and investigative practice due to the small number of criminal cases of this category sent to court; inconsistency of decisions taken by arbitration courts and courts of general jurisdiction on claims of legal entities and individuals against tax authorities; the ill-considered, legislative lack of regulation of the system of activities of regulatory and law enforcement agencies in every area. Keywords: tax offenses and crimes, prosecutorial supervision, sanctions Taking into account the problems arising in law enforcement practice, a radically new conceptual approach is proposed to change the current legislation, as well as to improve the activities of regulatory authorities, including by changing the structure of tax authorities. The role of the prosecutor's office in the prevention of tax offenses and crimes has been determined, proposals have been made on the need to amend the Law "On the Prosecutor's Office of the Russian Federation" in terms of setting tasks for the prevention of offenses and crimes. Taking into account the specifics of supervision, specific recommendations on its organization and implementation are given. Separate private methods of supervisory activities have been developed, as well as a system of measures to prevent tax offenses and crimes. The conducted research shows that when developing and fulfilling certain requirements, the role of the prosecutor's office in preventing tax offenses and crimes can be very significant. The means of prosecutorial supervision adopted have an impact on both the causes and conditions conducive to the commission of offenses in the area under consideration. The presented figures indicate the ever-increasing role of prosecutorial influence aimed at preventing tax offenses. Satisfaction of over 99% of claims allows us to assert a highly qualified approach of prosecutors to the protection of public interests in the field of taxation.